APLIKASI INJEKTOR PADA TUNGKU PELEBURAN PERUNGGU UNTUK MENINGKATKAN KINERJA PRODUKSI GAMELAN BALI - I G N Priambadi; I. G. K Sugita; I Putu Lokantara; I. M. Parwata; K Astawa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2014)
Gamelan melting process (casting) plays a role in the process of making Balinese gamelan. Furnace is a major component in this melting process. Craftmen use traditional melting furnace with an open form in which the air flow is needed in the injector fuel combustion using the straight shape. Injector of this model provides less air flow evenly so that the combustion process takes quite a long time. Ergo thermal injector has been introduced in service activities in the village craftmen group Tihingan Banjarangkan District of Klungkung. This furnace has the airflow coming out of the blower which then flows in a flow-shaped convergent-divergent. The function of this model is that the pressure of the incoming air flow passes into the air injectors to increase and spread evenly in the furnace chamber. Craftmen were trained directly how to make this model kitchen and directly transform traditional stoves with models furnace injector is introduced. The results showed that the combustion of fuel use was decreased by 12.96%. Fuel savings resulting from the latest injector models can provide the required distribution of air in the combustion process fuel (charcoal) to be more perfect and resulting high temperatures generated high. Supply of combustion air more evenly on the charcoal have an impact on the optimum combustion processKeywords: gamelan, injector, bronze alloys, smelting